Water uptake kinetics in soaking of grass pea - COSTA,Rui (2022)
Abstract Grass pea (Lathyrus sativus) is a pulse of great importance for food and feed due its high resistance to poor environmental conditions. However, it contains anti-nutritional factors and a neurotoxin, which is partially lost during soaking. A first approach to mass transfer during the soaking of grass pea was carried out by modeling the water uptake during soaking time using empirical mathematical models. The water uptake behavior was successfully described by the Peleg and the Exponential models, with these models showing several advantages when compared to the Mitscherlich and Page models. Both models estimated an increase of the equilibrium moisture content at temperatures between 50 °C and 100 °C, and detected an increasing effect of the area per volume ratio of the seed on the water uptake rate, but only at 75 °C and 100 °C. Additionally, grass pea presented a high true porosity, 13.651%, showing that it contains a large empty volume into which water can enter by capillary flow. Solids loss was observed to be high, varying from 18% at 25 °C to 44% at 100 °C for long soaking times, confirming that its effect in soaking cannot be neglected.